Oblikovanje za varnost - Stanič, Ivan (Urbani izziv, 1999)
Design for security against criminal acts is a made of preventive activity, whereby security measures are integrated in a cost efficient way, thus creating benefits for developers and future inhabitants. The article presents an example of an institutional activity carried out by the British police in promoting security in design, also intended for reducing fear from crime.
Keywords: crime; kriminal; mesta; security; stanovanjska naselja; stanovanjske četrti; urbanism; urbanistično planiranje; urbanizem; varnost; Velika Britanija